Spasi Artistik Interaktif untuk Anak (SAIA): Creative Business Model Proposal for Children's Interactive Art Space and Art Therapy - Augustin, Elfitra Mercredi; Larso, Dwi (The Indonesian Journal of Business Administration, 2013)
Plato, the Greek philosopher once opined that